Evaluasi Dan Perbaikan Proses Bisnis Menggunakan Quality Evaluation Framework (QEF), Root Cause Analysis (RCA) dan Business Process Improvement (BPI) (Studi Kasus: Pelayanan BPJS Rawat Inap Rumah Sakit Islam Aisyiyah Malang) - Muhammad Ibrahim Al Ghazi Saragi; Ismiarta Aknuranda; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Aisyiyah Islamic Hospital is one of the hospitals in Malang that collaborates with BPJS Kesehatan to provide health services, one of which is the inpatient BPJS service. In carrying out inpatient BPJS services, Aisyiyah Islamic Hospital has several problems that hinder the running of services such as lack of human resources, unbalanced workloads, inter-division miscommunication, and poor computer quality. To solve existing problems, it is necessary to evaluate the current business processes by modeling business processes using Business Process Model and Notation (BPMN). The next step is to evaluate business processes using the Quality Evaluation Framework (QEF) to determine the quality factor and the suitability of achieving the company's targets. From the results of the evaluation, an analysis was conducted to find the root of the problem using one of the Root Cause Analysis (RCA) techniques, namely Fishbone Analysis. The next step is to improve business processes using one of the methods of Business Process Improvement (BPI), namely streamlining. The results of the business process time analysis simulation of BPJS service inpatient care through the Polispesialis have a time reduction percentage of 26.69%. In addition, the business process of registering BPJS inpatient services through the UGD has a percentage reduction in time of 11.91% and in the business process of inpatient BPJS patient care has a time reduction percentage of 4.22%.